2022
DOI: 10.2807/1560-7917.es.2022.27.34.2100953
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of COVID-19 in the French overseas department Mayotte, 2020 to 2021

Abstract: Background During the COVID-19 pandemic, national and local measures were implemented on the island of Mayotte, a French overseas department in the Indian Ocean with critical socioeconomic and health indicators. Aim We aimed to describe the COVID-19 outbreak in Mayotte from March 2020 to March 2021, with two waves from 9 March to 31 December 2020 and from 1 January to 14 March 2021, linked to Beta (20H/501Y.V2) variant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
1
7
0
1
Order By: Relevance
“…For comparison during the peak of wave 1, 54 patients were hospitalized including 8 in ICU in a week. [10] This epidemiological situation could be explained by an increased transmissibility of VOC 20H/501Y.V2 compared to wild lineage. [4]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For comparison during the peak of wave 1, 54 patients were hospitalized including 8 in ICU in a week. [10] This epidemiological situation could be explained by an increased transmissibility of VOC 20H/501Y.V2 compared to wild lineage. [4]…”
Section: Discussionmentioning
confidence: 99%
“…For comparison during the peak of wave 1, 54 patients were hospitalized including 8 in ICU in a week. [10] This epidemiological situation could be explained by an increased transmissibility of VOC 20H/501Y.V2 compared to wild lineage. [4] We observed that delay between first signs and hospital admission was increased during wave 2, 7 days (4-9) versus 6 days (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dois artigos evidenciaram as semanas epidemiológicas e os picos de óbito materno no ano de 2020, sendo em um estudo descrito o pico de casos e óbitos entre as semanas epidemiológicas 17 e 30 (NAKAMURA-PEREIRA, et al, 2021). E em outro estudo (LÓPEZ-RODRIGUEZ, et al, 2021) foi destacado que os dois primeiros casos foram registrados na semana epidemiológica 15 de óbito materno, e o pico ocorreu na semana 28, responsável por 17,5% do total de casos de óbito maternos.Outros estudos reforçam os dados encontrados acima, principalmente relacionado aos picos da pandêmica e a primeira onda que se espalhou rapidamente no ano de 2020.O pico de óbitos da COVID-19 proporcional a toda a população ocorreu na semana epidemiológica 18 no ano de 2020, com o alcance de 39%(SUBIROS et al, 2022), fato relatado também em outra pesquisa onde o pico de mortes é descrita nas semanas epidemiológicas 17 a 20 no ano de 2020(ORELLANA et al, 2021)…”
unclassified